Parametric study of ground-track based performance measure requirements for the optimization of near earth twin-spacecrafts trajectory. - Djojodihardjo, Harijono; A. Gunter, A. Aq'Grabin; Varatharajoo, Renuganth (2012)
Parametric optimization study is carried out on Performance Measure for assessing the benefits of relevant ground-track parameters and Instantaneous Overlap Area (IOA) in near earthand near-equatorial twin-satellite formation flying to explore its potential as space platform oriented towards Tropical Resources and Environment Monitoring mission. The present study also emphasizes two aspects: the dynamics of relative motion of multiple spacecrafts and the desirable ground tracks such missions. Relative motion dynamics incorporating Clohessy-Wiltshire Equation for circular orbits is used as a reference. The performance metric is synthesized as a tradeoff between exact definition and intuitive judgment.